Retention of indoxyl sulfate in different genotypes of ABCC2 may explain variation in tacrolimus pharmacokinetics - Wang,Jing; Huang,Siqi; Li,Yuanchen; Fang,Qiu; Wang,Min; Zhu,Huaijun (PeerJ, 2024)
Background Microbiota-derived toxins indoxyl sulfate and hippuric acid were previously reported to be associated with altered pharmacokinetics of the immunosuppressant tacrolimus in liver transplant recipients, and ABC transporter proteins are likely to be involved in the transport of such substances, but the in vivo role has not been elucidated. The aim of this study was to assess the retention of indoxyl sulfate and hippuric acid in the plasma of liver transplantation subjects carrying different genotypes of ABCB1 and ABCC2 (changes in transporter activity due to genetic variation), and to explore whether genetic variation is involved in altering the relationship between microbe-derived toxins and tacrolimus pharmacokinetics. Methods Liver transplantation subjects treated with the immunosuppressive regimen tacrolimus, corticosteroids, and mycophyolate mofetil were included and divided into normal renal function group and chronic kidney disease group. The plasma concentrations of indoxyl sulfate and hippuric acid in two groups of liver transplantation subjects carrying different genotypes of ABCB1 and ABCC2 were compared. For genotype carriers with significant differences, the Pearson Correlation Coefficient method was further used to investigate the correlation between plasma indoxyl sulfate level and tacrolimus dose-corrected trough concentration in patients with different renal function status. Results Carriers of the rs717620-24T variant exhibited high plasma indoxyl sulfate retention in patients with normal renal function, and furthermore, chronic kidney disease patients and patients with normal renal function exhibited indoxyl sulfate and tacrolimus in the ABCC2 normal function (β = −0.740, p = 0.020) and reduced function groups (β = −0.526, p = 0.005), respectively, showing a strong correlation with tacrolimus. Conclusion ABCC2 may be one of the pathways by which tacrolimus pharmacokinetics is altered by indoxyl sulfate.
Keywords: Liver transplantation; Indoxyl sulfate; ABCC2; Single nucleotide polymorphisms; Tacrolimus pharmacokinetics